TINGKAT KERUSAKAN SEL DARAH MERAH LELE DUMBO (Clarias gariepinus) YANG DIPAPARKAN DALAM ENDOSULFAN PADA KONSENTRASI SUBLETAL - Indra Gumay Yudha (Universitas Gadjah Mada, 2006)
The objective of this experiment was to study the effect of endosulfan on red blood cells of catfish, C. gariepinus. Ten fishes, (2-3 g of body weight), were kept in 30 l fish tank. Fish were exposed to 5 concentrations of endosulfan (1.71 ppb, 3.43 ppb, 5.14 ppb, 6.85 ppb and 8.57 ppb) for 6 weeks. The experiment was done in triplicates. The result showed that endosulfan caused the red blood cells damage by forming cerroids and lipofuscin complex. This impairment was over 90% of total red blood cells when fishes were exposured to endosulfan at 6.85-8.57 ppb.